2013
DOI: 10.17711/sm.0185-3325.2013.004
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de heroína inyectada en Colombia y comportamientos de riesgo

Abstract: SUMMARY ObjectiveTo determine socio-demographic characteristics, prevalence of HIV risk, behaviors use. MethodsWe performed a cross-sectional study using sampling generated by the respondent; the sample consisted of 540 participants (Pereira: n=300; Medellín: n=240) over 18 years. The interview was conducted by an expert in counseling for HIV and sexually transmitted diseases. Ethical requirements were met. We used the software RDSAT. ResultsThere are extensive networks of IDUs in both cities. The population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…There are few studies on hepatitis C in Colombia 32 , and this investigation identified a significant number of injection drugs users who share and reuse injection equipment, similarly to what was observed in other cities of Colombia in 2010 [33][34][35] ; widely documented and discussed factors in other countries, though for Colombia, represent the first step toward intervention strategies 36 . Co-infections of HIV and HCV have been reported among drug users in different countries.…”
Section: Discusionsupporting
confidence: 63%
“…There are few studies on hepatitis C in Colombia 32 , and this investigation identified a significant number of injection drugs users who share and reuse injection equipment, similarly to what was observed in other cities of Colombia in 2010 [33][34][35] ; widely documented and discussed factors in other countries, though for Colombia, represent the first step toward intervention strategies 36 . Co-infections of HIV and HCV have been reported among drug users in different countries.…”
Section: Discusionsupporting
confidence: 63%
“…Bogotá, the Colombian capital, is the city with the largest population in Colombia, and is the main economic, cultural, political, and industrial centre in the country (Gobierno de Colombia, 2013; Perez, 2010). Armenia, located in the Andean region southwest of Bogotá (Berbesi-Fernández et al, 2015); Cúcuta, located in the country’s northeast, borders with Venezuela (DANE, 2005); and Pereira, located in western Colombia’s coffee-growing region and has previously been shown to exhibit high rates of injection drug use (Berbesi, Segura-Cardona, Montoya-Vélez, & Mateu-Gelabert, 2013). Due to the lack of previous studies regarding HCV infection in PWID in Colombia, these cities were selected as the best possible approach to develop evidencebased knowledge of HCV prevalence and risk factors of PWID across Colombia.…”
Section: Methodsmentioning
confidence: 99%
“…Participant data were collected through a survey technique with a previously applied and reviewed form of PWID (Berbesi et al, 2012) based on the instrument designed by the World Health Organization (WHO) in Bogota (Mejía & Gómez, 2005). This questionnaire examines demographic characteristics (age, sex, primary income source and familial socioeconomic status), injection risk behaviors (Daily injection rate, Syringe or needle acquisition from a drug dealer, self-financing of drug consumption, confiscation of injection equipment by police or any authority, giving or selling used syringes, injecting another person and using encapsulated or ready to use drug vial), equipment exchange conducts (Sharing syringes, needles, and paraphernalia such as cotton, filter, water, and mixer) within the last six months and the last reported injection episode, and ever presenting injection-related harms (suffering an opium or heroin overdose and knowing someone who suffered an overdose).…”
Section: Methodsmentioning
confidence: 99%